2009
DOI: 10.1088/0963-0252/19/1/015007
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the effect of atomic and molecular metastable state excitation on air plasma composition behind strong shock waves

Abstract: A detailed analysis of the processes of charged and neutral species formation in N 2 -O 2 -Ar system behind strong shock waves is conducted on the basis of an extended thermally non-equilibrium kinetic model with careful allowance of reactions with electronically excited atoms and molecules and vibration-electron-chemistry coupling. The model is validated against experimental data such as measurements of electron number density behind the strong shock wave front, temporal profile of O 2 vibrational temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 49 publications
(58 reference statements)
0
47
0
Order By: Relevance
“…Atomic species can be electronically excited or ionized. The rate coefficients of some of these processes under heavy particle impact have been reported by Capitelli et al 22 and Starik et al 39 They have been used in the present study. Otherwise, the rate coefficient…”
Section: Electronic Excitation and Ionizationmentioning
confidence: 98%
See 2 more Smart Citations
“…Atomic species can be electronically excited or ionized. The rate coefficients of some of these processes under heavy particle impact have been reported by Capitelli et al 22 and Starik et al 39 They have been used in the present study. Otherwise, the rate coefficient…”
Section: Electronic Excitation and Ionizationmentioning
confidence: 98%
“…The electron density is negligibly small. The related rate coefficients have been taken from Capitelli et al, 22 Kossyi et al, 38 Park, 30 and Starik et al 39 Few data can be found in the literature for theses processes. When the rate coefficient is not reported in the previous references, we have used data due to Park et al, 40 Bhadra and Ghosh, 41 and Drawin 42 to derive the analytical form…”
Section: Electronic Excitation and Ionizationmentioning
confidence: 99%
See 1 more Smart Citation
“…• vibrational processes (vibrational excitation under electron, N 2 and N impact) [7][8][9], • dissociation of electronic excited states of N 2 and of all electronic states of N + 2 under electron impact [10], • electronic excitation under electron, N 2 and N impact [3,10,11,[13][14][15][16]18], • excitation transfer [11,17,18],…”
Section: Implementation Of the Cr Model Coram-nmentioning
confidence: 99%
“…The equations have been modified in order to take into account reacting gas mixtures following Eqs. (3) to (6) [26][27][28][29][30][31][32]. The populations of the radiating electronic states of molecules, which are considered as independent chemical species in the model [33], are calculated by solving the corresponding kinetic equations.…”
Section: Multi-temperature Kinetics and Just-overlapping Line Modelmentioning
confidence: 99%